Analisis pola persebaran TPA dan TPS serta strategi pengelolaan sampah di Kabupaten Pasaman Barat - Pratama, Tomi; Nefilinda, Nefilinda; Rezki, Afrital (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Lack of optimal waste management in West Pasaman, such as insufficient number of TPS, infrastructure, open dumping waste management system, road access to the TPA, etc becomes a background of this research. The research aims to determine the distribution pattern of TPA and TPS in West Pasaman. The types of data used are primary and secondary data. Data collection techniques use observation, interviews, questionnaires, and documentation. Technical data analysis uses nearest neighbor analysis and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in preparing strategies. The results of the research on the distribution pattern of TPA and TPS using clustered Nearest Neighbor Ratio was 0.631306 (Clustered). Waste generation in West Pasaman based on population of 442,479, was 2.4 kg/person/day. The remaining landfill capacity is 80,000 m3 (8 Ha) of the 10 Ha total landfill area. The S-O (Strengths, Opportunities) strategy utilizes collaboration with stakeholders in outreach to the community. The W-O (Weakness, Opportunities) strategy optimizes the Local Government regulation to strengthen operational funds for waste management. S-T (Strengths, Threats) strategy, optimizing human resources through a forum for communicating the importance of waste management. The W-T (Weakness, Threats) strategy creates a TPA structure in management.